Magnetic Resonance Imaging combined with Computed Tomography in the Diagnosis of Multiple Myeloma and the Killing Effect of Doxorubicin Nano-drug Delivery System on Myeloma Cells: Effect of Doxorubicin Nano-drug Delivery System on Myeloma Cells - Liao, Junjie; Yu, Zhongqiang; Rui, Mingzhong; Wang, Yonghao (Cellular and Molecular Biology, 2022)
It was to adopt magnetic resonance imaging (MRI) combined with computed tomography (CT) to diagnose multiple myeloma (MM) and evaluate the therapeutic effect of the doxorubicin nano-drug delivery system on MM, providing a more effective method for the treatment of MM. For this aim, eighty-eight patients with MM admitted to our Hospital from June 2019 to July 2020.7 were selected as study subjects and divided into a control group (treated with doxorubicin) and an observation group (treated with doxorubicin-loaded nanoparticles) according to the random number table, 44 cases for each group. MRI and CT were used to examine the two groups of patients to assess the clinical efficacy and side effects of the two treatments and to compare the myeloma cell survival rate and apoptosis rate. Results showed that the diameter of nanoparticles was about 50 nm, the particle size was uniform, the distribution was dense, and the stability was good; the lesion was well-circumscribed on CT scan, and a soft tissue mass could be detected on MRI. The number of patients with effective treatment in the observation group was significantly higher than that in the control group (42 cases vs 34 cases) (P< 0.05); the number of patients with small plate reduction, increased myocardial enzymes, alopecia, liver failure, gastrointestinal reactions, peripheral neuritis, and other adverse reactions in the observation group was significantly lower than that in the control group (total number of patients 48 vs 101) (P< 0.05); the survival rate of myeloma cells in the observation group was obviously inferior to that in the control group (61.3 % vs 88.31 %) (P< 0.05). Conclusion: MRI combined with CT examination can be better used for the diagnosis of the disease, and the study shows that doxorubicin nano-drug delivery preparation is safer and more effective in the treatment of MM disease, which is worthy of clinical promotion.